Rancang Bangun Decision Support System (DSS) Untuk Membantu Menentukan Hasil Seleksi Pegawai Pada Politeknik Negeri Cilacap Dengan Menggunakan Metode Perbandingan Eksponensial (MPE) - Riyadi Purwanto (Politeknik Harapan Bersama, 2018)
Information Technology has provided an important role as a communication medium to support the business processes of industry / companies, government agencies, and educational institutions. One form of utilization of information technology is as a media Decision support system (DSS) that can be used to assist decision-making for a leader. Decision Support System (DSS) is an interactive information system that provides information, modeling, and data manipulation. The system is used to assist decision making in semi-structured situations and structured situations, where nobody knows exactly how decisions should be made. At this time the process of employee selection on the PNC is still done conventionally, causing several problems, among others: 1)Often miscalculated value skors, 2)Factors like and dislike very high, 3)Sometimes the leadership has difficulty when determining the right employee to be accepted based on predetermined criteria. Looking at the existing problems, it is necessary to develop Decision Support System (Decision Support System) that can help the leadership of Cilacap State Polytechnic to determine the result of new Employee selection in Cilacap State Polytechnic environment based on predetermined criteria. The system was developed using the Exponential Comparison Method (MPE)